2020
DOI: 10.25259/sni_578_2019
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cerebral vasoconstriction syndrome concomitant with cerebral venous sinus thrombosis following ovarian tumor resection: A report of two cases

Abstract: Background: Reversible cerebral vasoconstriction syndrome (RCVS) presents with characteristic clinical, brain imaging, and angiographic findings. The most common clinical feature of RCVS is a severe acute headache, which is often referred to as a thunderclap headache due to the nature of its presentation. It may occur spontaneously or may be provoked by various precipitating factors. We present a rare case of RCVS concomitant with cerebral venous sinus thrombosis (CVST) in a woman who underwent resection of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…9 One case series of 2 women who were each diagnosed with both RCVS and cerebral venous thrombosis after ovarian tumor resection suggested that the ovarian tumor was associated with the venous thrombosis, while the rapid decreases in estrogen following surgery may have triggered RCVS. 10…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 One case series of 2 women who were each diagnosed with both RCVS and cerebral venous thrombosis after ovarian tumor resection suggested that the ovarian tumor was associated with the venous thrombosis, while the rapid decreases in estrogen following surgery may have triggered RCVS. 10…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…RCVS and Female Sex diagnosed with both RCVS and cerebral venous thrombosis after ovarian tumor resection suggested that the ovarian tumor was associated with the venous thrombosis, while the rapid decreases in estrogen following surgery may have triggered RCVS. 10 In a comparison of RCVS among men, nonpregnant women, and postpartum women, Topcuoglu et al 6 found that nonpregnant women were older and more likely to have had prior migraine and serotonergic antidepressant use. Postpartum patients were younger and had less vasoconstrictive drug use than nonpregnant women.…”
Section: Nelsonmentioning
confidence: 99%
See 1 more Smart Citation